2014
DOI: 10.14260/jemds/2014/2027
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Placebo Controlled Study of Preoperative Pregabalin on Postcholecystectomy Pain Relief

Abstract: There are studies that have demonstrated the role of pregabalin as a pre-emptic analgesic in the multimodal therapy for acute postoperative pain management. However, its use in more painful operative procedures like open cholecystectomy are limited and hence the present study was undertaken to evaluate the effectiveness of a single dose of preoperative oral pregabalin in attenuating the postoperative pain. In this randomized, controlled, prospective and double blind study, 80 patients (ASA I & II, aged 18-55 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…33 Many studies assessing preoperative 150 mg pregabalin efficacy on postoperative pain after operations performed with different anesthesia and surgical methods have also shown fewer side effects due to reduced opioid consumption. 17,24 As a result of all this information; we reached the conclusion that the preoperative use of Pregabalin 150 mg 12 hours and 1 hour prior to surgery reduced preoperative anxiety, provided postoperative analgesia, reduced analgesic consumption and associated side effects, thus proving to be superior to placebo. However, in order for pregabalin to be used as routine premedication, larger sample groups and studies with different doses are required.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…33 Many studies assessing preoperative 150 mg pregabalin efficacy on postoperative pain after operations performed with different anesthesia and surgical methods have also shown fewer side effects due to reduced opioid consumption. 17,24 As a result of all this information; we reached the conclusion that the preoperative use of Pregabalin 150 mg 12 hours and 1 hour prior to surgery reduced preoperative anxiety, provided postoperative analgesia, reduced analgesic consumption and associated side effects, thus proving to be superior to placebo. However, in order for pregabalin to be used as routine premedication, larger sample groups and studies with different doses are required.…”
Section: Discussionmentioning
confidence: 91%
“…In response to these studies on the suppressive effect of preoperative pregabalin on hemodynamic parameters, Upendra et al concluded that hemodynamic parameters did not change after preoperative pregabalin 150 mg in their study including 80 patients who underwent cholecystectom. 24 Again, as a result of a prospective, placebo-controlled study including 60 patients with axillary block, Pürcü et al reached the conclusion that pregabalin did not affect hemodynamic parameters after a single dose of preoperative pregabalin 150 mg. 25 In their placebo-controlled studies on the effects of pregabalin 75 mg and 150 mg premedication on hemodynamic responses, Rastogi et al have concluded that the premedication did not result in a clinically significant respiratory depression and reduction in oxygen saturation. 26 In our study, no changes in favor of desaturation in intraoperative peripheral oxygen saturation values were observed in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation